Mesenchymal stromal cells from pooled mononuclear cells of multiple bone marrow donors as rescue therapy in pediatric severe steroid-refractory graft-versus-host disease: a multicenter survey - Kuçi, Zyrafete; Jauch, Anna; Janssen, Johannes W. G.; Greil, Johann (Haematologica, 2016)
To circumvent donor-to-donor heterogeneity which may lead to inconsistent results after treatment of acute graft-versus-host disease with mesenchymal stromal cells generated from single donors we developed a novel approach by generating these cells from pooled bone marrow mononuclear cells of 8 healthy “3rd-party” donors. Generated cells were frozen in 209 vials and designated as mesenchymal stromal cell bank. These vials served as a source for generation of clinical grade mesenchymal stromal cell end-products, which exhibited typical mesenchymal stromal cell phenotype, trilineage differentiation potential and at later passages expressed replicative senescence-related markers (p21 and p16). Genetic analysis demonstrated their genomic stability (normal karyotype and a diploid pattern). Importantly, clinical end-products exerted a significantly higher allosuppressive potential than the mean allosuppressive potential of mesenchymal stromal cells generated from the same donors individually. Administration of 81 mesenchymal stromal cell end-products to 26 patients with severe steroid-resistant acute graft-versus-host disease in 7 stem cell transplant centers who were refractory to many lines of treatment, induced a 77% overall response at the primary end point (day 28). Remarkably, although the cohort of patients was highly challenging (96% grade III/IV and only 4% grade II graft-versus-host disease), after treatment with mesenchymal stromal cell end-products the overall survival rate at two years follow up was 71±11% for the entire patient cohort, compared to 51.4±9.0% in graft-versus-host disease clinical studies, in which mesenchymal stromal cells were derived from single donors. Mesenchymal stromal cell end-products may, therefore, provide a novel therapeutic tool for the effective treatment of severe acute graft-versus-host disease.